Manual der Arbeitsgruppe Interventionelle Kardiologie (AGIK) der Deutschen Gesellschaft für Kardiologie – Herz- und Kreislaufforschung e.V. (DGK) - Teil 2: „Durchführung der perkutanen Koronarintervention“ - Nef, Holger M.; Achenbach, Stephan; Birkemeyer, Ralf; Bufe, Alexander; Doerr, Oliver; Elsaesser, Albrecht; Gaede, Luise; Gori, Tommaso; Hoffmeister, Hans M.; Hofmann, Felix J.; Katus, Hugo A.; Liebetrau, Christoph; et al. (Der Kardiologe, 2021)
This manual addressing the interventional treatment (part 2) is a recommendation for interventional cardiologists. It displays the latest evidence in interventional cardiology. Each chapter was designed to focus on the everyday practicability and to provide decision support for cardiologists in the daily clinical routine of a catheter laboratory. Despite the practical advice by many experts, this manual cannot replace the medical evaluation of each individual patient and thus an adaptation of the diagnostics or treatment is necessary.
CRIS-Team WoS Importer:2021-10-08